Rationing as a Normative Principle of Ecosystem Interaction’s Financing - N. M. Abdikeev; I. M. Stepnov; J. A. Kovalchuk (Финансы: теория и практика, 2024)
The relevance of the study is confirmed by the fact that it is financial relations in ecosystems that have become the subject of research that are influenced by certain rules (including state regulation) that limit the degrees of freedom of ecosystem participants and its organizers and ultimately determine the viability of the ecosystem approach, which determined the purpose of the study as establishing the potential of the financial instruments of the state in ensuring the necessary level of rationing for regulation in business ecosystems.   It is shown that the distinctive feature between the corporate and ecosystem approach is the use of rationing as additional restrictions to financial decisions based on public and private sources of financial resources available in business ecosystems. Research methods, on the one hand, are based on a key methodology — the emerging ecosystem’s theory in the part where it replaces the firm’s theory, taking into account the provisions of the credit rationing theory as an application to corporate finance, on the other hand, the conceptual provisions of the theory of constraints in relation to finance are taken into account. The results of the study show that the allocation of public and private ecosystem rationing makes it possible to form the basis for strategic financial decisions. It is established that when creating an industrial business ecosystem, small and medium-sized businesses will become its main participants, which is justified by the need for external financing that the business ecosystem can provide. It is concluded that when implementing the idea of rationing, the search for the optimal strategy for participants can be simplified to considering only pair interaction (instead of optimizing the entire set of relationships). The presented paired partitions make it possible to clarify the constraints and individualize them. Comparative analysis has shown that, from the point of view of effective implementation of restrictions, the consortium with state participation has the greatest potential, and clusters have the least potential, from the point of view of capital rationing. As a result, the conclusion is made about the prospects for the development of business ecosystems with state financing (control), which would imply a purposeful solution to the tasks of the state in the modern economy.